2016
DOI: 10.1002/phar.1795
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Effective Use of Pharmacologic and Device Therapy for Peripartum Cardiomyopathy

Abstract: Peripartum cardiomyopathy (PPCM) is an uncommon, idiopathic complication of pregnancy associated with significant (10-30%) mortality. The disease occurs late in pregnancy or in the months following delivery, resulting in reduced systolic function and heart failure (HF) symptoms. Limited direction is provided for the management of PPCM, and the safe and effective use of medications in pregnant and breastfeeding women with PPCM presents a unique challenge. Although several HF therapies in pregnant and lactating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
(291 reference statements)
0
3
0
Order By: Relevance
“…Hydralazine and nitrates may be used as vasodilator therapy. On the basis of the RALES and EMPHASIS-HF trials,120121 mineralocorticoid receptor antagonists are indicated in patients with NYHA II-IV heart failure and an LVEF ≤35%114; these agents should be avoided during pregnancy because of their anti-androgenic effects117 but may be used during breast feeding 122. Digoxin may be used safely in pregnancy 123…”
Section: Management Of Peripartum Cardiomyopathymentioning
confidence: 99%
“…Hydralazine and nitrates may be used as vasodilator therapy. On the basis of the RALES and EMPHASIS-HF trials,120121 mineralocorticoid receptor antagonists are indicated in patients with NYHA II-IV heart failure and an LVEF ≤35%114; these agents should be avoided during pregnancy because of their anti-androgenic effects117 but may be used during breast feeding 122. Digoxin may be used safely in pregnancy 123…”
Section: Management Of Peripartum Cardiomyopathymentioning
confidence: 99%
“…All angiotensin converting enzyme inhibitors, angiotensin receptor blockers, including sacubitril-valsartan are contraindicated in pregnant women [42]. Mineralocorticoid receptor antagonists should be avoided during pregnancy in view of their anti-androgenic effects, although they may be taken during breast feeding [43]. Digoxin may be safely used in pregnancy [44].…”
Section: Managementmentioning
confidence: 99%
“…However, intra-aortic balloon pumps, extracorporeal circulatory devices, and even left ventricular assist devices have been used during pregnancy. 144,145 Women with a history of peripartum cardiomyopathy are at risk of recurrence in a future pregnancy, even those who seem to have clinically and echocardiographically recovered.…”
Section: Peripartum Cardiomyopathymentioning
confidence: 99%